2007
DOI: 10.1007/s00114-007-0244-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a male-produced pheromone in Tetropium fuscum (F.) and Tetropium cinnamopterum (Kirby) (Coleoptera: Cerambycidae)

Abstract: (E)-6,10-dimethyl-5,9-undecadien-2-ol (geranyl acetol), termed here fuscol, was identified as a male-produced pheromone emitted by Tetropium fuscum (F.) and Tetropium cinnamopterum Kirby. In field experiments, traps baited with synthetic fuscol alone were not significantly attractive, but the combination of fuscol plus host volatiles (a synthetic blend of monoterpenes plus ethanol) attracted significantly more male and female T. fuscum and female T. cinnamopterum than did host volatiles alone. This is the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 9 publications
7
88
1
Order By: Relevance
“…In addition to chemical cues, A. malasiaca use visual cues so that traps with visual targets may be effective. Since the increase of trap catches are reported after combinations of male sex pheromone and floral attractant or host volatiles in the longicorn beetle, Anaglyptus subfasciatus and Tetropium fuscum (Nakamuta et al, 1997;Silk et al, 2007), combinations of two or more factors may be effective. An alternative insecticide system is also considered: contact with insecticide that would kill the beetle.…”
Section: Suggestion For More Efficient Con-trol Methods For a Malasiacamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to chemical cues, A. malasiaca use visual cues so that traps with visual targets may be effective. Since the increase of trap catches are reported after combinations of male sex pheromone and floral attractant or host volatiles in the longicorn beetle, Anaglyptus subfasciatus and Tetropium fuscum (Nakamuta et al, 1997;Silk et al, 2007), combinations of two or more factors may be effective. An alternative insecticide system is also considered: contact with insecticide that would kill the beetle.…”
Section: Suggestion For More Efficient Con-trol Methods For a Malasiacamentioning
confidence: 99%
“…However, only a few reports clarify attractive chemicals in the plant volatiles and attraction of the beetles in the field (Sakai and Yamasaki, 1990;Allison et al, 2004 references cited therein). In Tetropium fuscum and T. cinnamopterum (Spondylinae), male-produced pheromone plus host plant volatiles attract more adults in the field (Silk et al, 2007). Outside the family Cerambycidae, males of a cockchafer (Melolontha spp.…”
Section: Mate Location In Cerambycidaementioning
confidence: 99%
“…For example, males of many species in the subfamily Cerambycinae produce pheromones composed of isomers of 3-hydroxy-2-hexanone and/or 2,3-hexanediol, to which both sexes are attracted (Lacey et al 2004(Lacey et al , 2007(Lacey et al , 2008Hanks et al 2007). Similarly, the terpenoid alcohol (E)-6,10-dimethyl-5,9-undecadien-2-ol, termed "fuscumol", is a male-produced pheromone of some species in the subfamily Aseminae (Silk et al 2007), but the same compound and its acetate have recently been shown to attract many species in the subfamily Lamiinae as well (Mitchell et al 2011).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…This type of hybridisation can occur when two closely related species are brought together through anthropogenic actions (e.g., inadvertent long distance dispersal facilitated by international trade) that place these species geographically close enough together. The introduction of exotic insects may also lead to interspecific hybridisation; as determined by Silk et al (2007) and used by Rhainds et al (2011), the exotic T. fuscum and the native T. cinnamopterum share a common sex/aggregation pheromone. This leads to the question "What is the potential for intraspecific hybridisation between these species that respond to the same pheromone?…”
Section: Resultsmentioning
confidence: 99%